Denosumab use in osteogenesis imperfecta: an update on therapeutic approaches - Fatma Majdoub; Hanene Lassoued Ferjani; Dorra Ben Nessib; Dhia Kaffel; Kaouther Maatallah; Wafa Hamdi (Annals of Pediatric Endocrinology & Metabolism, 2023)
Osteogenesis imperfecta (OI) is an inherited skeletal disorder that leads to bone fragility and multiple fractures. Given advances in the genetic understanding of existing phenotypes and newly discovered mutations, therapeutic management of OI has become challenging. Denosumab, a monoclonal antibody that inhibits the interaction between the receptor activator of nuclear factor kappa B ligand (RANKL) and its receptor RANK, has been approved to treat postmenopausal osteoporosis and emerged as an important therapy for malignancies and other skeletal disorders, including pediatric skeletal conditions such as OI. This review summarizes information about denosumab therapy in OI by exploring its mechanisms of action, main indications, and safety and efficacy. Several case reports and small series have been published about the short-term use of denosumab in children with OI. Denosumab was considered a strong drug candidate for OI patients with bone fragility and a high risk of fracture, particularly for patients with the bisphosphonate (BP)-unresponsive OI-VI subtype. The evidence for denosumab's effects in children with OI indicates that it effectively improves bone mineral density but not fracture rates. A decrease in bone resorption markers was observed after each treatment. Safety was assessed by tracking the effects on calcium homeostasis and reporting side effects. No severe adverse effects were reported. Hypercalciuria and moderate hypercalcemia were reported, suggesting that BPs be used to prevent the bone rebound effect. In other words, denosumab can be used as a targeted intervention in children with OI. The posology and administration protocol require more investigation to achieve secure efficiency.